Analisis Kondisi Fisik pada Atlet Pencak Silat Persaudaraan Setia Hati Terate (PSHT) di Ranting Tanggunggunung Cabang Tulungagung - Wulandari, Dini Nur; Puspodari; Bekti, Ruruh Andayani (SPRINTER: Jurnal Ilmu Olahraga, 2024)
The purpose of the study was to determine the physical condition of the martial arts athletes of the Persaudaraan Setia Hati Terate (PSHT) in the Tulungagung Branch of Tanggunggunung. This study utilised a descriptive quantitative approach with a survey method. The survey method was chosen to collect information or data regarding a large population by utilising a smaller sample. The sample in this study was 25 athletes. The instruments used were tests and measurements of 7 physical condition items, namely: strength (Push Up and Sit Up tests), agility (alternating running test), speed (30 metre sprint test), eye and hand coordination (Ball Wall Pass test), endurance (VO₂Max test), and balance (Stork Stand test). The results of this study are (1) The Physical Condition of the Push Up strength of PSHT Pencak Silat athletes in the Tulungagung Branch of Tanggunggunung Branch 60% is included in the very good criteria and 40% is included in the good criteria. (2) The physical condition of Sit Up strength 16% falls into very good criteria, 64% falls into good criteria and 20% falls into moderate criteria. (3) Physical condition of 30 metre sprint speed 12% falls into excellent criteria, 32% falls into the good category and 56% falls into moderate criteria. (4) Physical condition of agility running back and forth 40% falls into good criteria and 60% falls into moderate criteria. (5) The physical condition of Ball Wall Pass eye-hand coordination 24% falls into the excellent criteria, 72% falls into the good category and 4% falls into the moderate criteria.